2021
DOI: 10.1182/blood-2021-152160
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Assessment of CDR101 - a BCMAxCD3xPD-L1 Trispecific Antibody with Superior Anti-Tumor Efficacy

Abstract: BCMAxCD3 targeting therapies have demonstrated anti-myeloma activity, and high minimal residual disease negativity rates can be achieved with this approach in heavily pre-treated patients with relapsed or refractory multiple myeloma (RRMM). Despite these promising clinical results, patients eventually develop resistant disease and relapse. Thus, there is a high need for novel BCMA therapies that can evade the resistance mechanisms and provide more durable responses. Recently, we reported on the promising activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The phase I clinical trial is ongoing, whose preliminary results showed us that the maximum safe dose of HPN217 was 2,150 µg/week and its treatment-emergent AEs were transient and controllable ( 33 ). Another BCMA-targeted tri-specific agent who was undergoing preclinical evaluation has been reported in this meeting as well ( 35 ). CDR101, targeting CD3, BCMA, and PD-L1, could guide T cells to BCMA-expressed tumor cells and play a role in combating immunosuppression caused by the interaction of PD-L1 and PD-1 at the immune synapse site, which may reduce the possibility of “on-target off-tumor” effects.…”
Section: Progress Of Bcma-targeted Immunotherapiesmentioning
confidence: 97%
“…The phase I clinical trial is ongoing, whose preliminary results showed us that the maximum safe dose of HPN217 was 2,150 µg/week and its treatment-emergent AEs were transient and controllable ( 33 ). Another BCMA-targeted tri-specific agent who was undergoing preclinical evaluation has been reported in this meeting as well ( 35 ). CDR101, targeting CD3, BCMA, and PD-L1, could guide T cells to BCMA-expressed tumor cells and play a role in combating immunosuppression caused by the interaction of PD-L1 and PD-1 at the immune synapse site, which may reduce the possibility of “on-target off-tumor” effects.…”
Section: Progress Of Bcma-targeted Immunotherapiesmentioning
confidence: 97%
“…Another group has generated a novel trispecific antibody (CDR101) which recognizes BCMA, CD3 and PD-L1. This antibody induced stronger and more durable responses than a BCMA BsAb control in a murine model of MM [ 71 ]. In the clinical setting, the TRIMM-3 study is a non-randomised phase 1b study in RRMM, where patients receive either teclistamab or the G protein-coupled receptor, class C, group 5, member D (GPRC5D)-directed BsAb talquetamab, in combination with a PD-1 inhibitor (NCT05338775).…”
Section: Checkpoint Inhibitors (Cpi)mentioning
confidence: 99%
“…The evidence base for bsAb therapies in multiple myeloma has been reviewed elsewhere, and the BCMA-targeting bsAb teclistamab has recently gained regulatory approval in Europe and the United States (141)(142)(143)(144)(145)(146). While certain considerations like lengthy vein-to-vein times are unique to autologous CAR-T therapies, other strategies discussed herein such as the addition of GSIs or PD-1 blockade may be beneficial to BCMA-targeting bsAbs as well (147)(148)(149). Similarly, some of these approaches are also relevant to products relying on genetic manipulation of the native TCR itself (150)(151)(152).…”
Section: Discussionmentioning
confidence: 99%